Exploring the Link Between Critical Thinking Styles and Students’ Critical Thinking Ability in Biology Education - Khacera Juliyanti; Jayanti Syahfitri (AL-ISHLAH: Jurnal Pendidikan, 2024)
Critical thinking style reflects how students apply their critical thinking skills, playing a crucial role in developing their overall ability to think critically. This study explores the relationship between high school students' critical thinking styles and their critical thinking abilities. The research involved 112 high school students who completed the YCCST instrument both as a pretest and posttest. Data were analyzed using correlation and regression tests, ensuring normal distribution (0.200 0.05) and linearity (0.277 0.05). The findings revealed a strong positive correlation (r = 0.714) between critical thinking styles and critical thinking ability. Regression analysis indicated that critical thinking style accounts for 51% of the variance in critical thinking ability. These results suggest that students' critical thinking styles significantly influence their ability to think critically. Educators can utilize this information by identifying students’ thinking styles as a foundation for selecting appropriate teaching materials and learning methods, ultimately enhancing students' critical thinking skills. This study underscores the importance of assessing and incorporating students' thinking styles into educational practices to foster their critical thinking development. Future research could expand on these findings by exploring diverse educational settings and additional influencing factors.